2013
DOI: 10.1007/s00221-013-3527-z
|View full text |Cite
|
Sign up to set email alerts
|

Grip-force modulation in multi-finger prehension during wrist flexion and extension

Abstract: Extrinsic digit muscles contribute to both fingertip forces and wrist movements (FDP and FPL – flexion, EDC - extension). Hence it is expected that finger forces depend on the wrist movement and position. We investigated the relation between grip force and wrist kinematics to examine whether and how the force: (1) scales with wrist flexion-extension (FE) angle; (2) can be predicted from accelerations induced during FE movement. In one experiment subjects naturally held an instrumented handle using a prismatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
7
13
0
Order By: Relevance
“…While AS varied, this variation was limited to postures in a close proximity to the fully flexed wrist position. This observation is consistent with our earlier study (Ambike et al 2013) wherein the “natural grip force” for the extreme wrist flexion was higher than for all other wrist positions. Other wrist positions had no effect on AS; so, for those positions Hypothesis-1 is rejected by the data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While AS varied, this variation was limited to postures in a close proximity to the fully flexed wrist position. This observation is consistent with our earlier study (Ambike et al 2013) wherein the “natural grip force” for the extreme wrist flexion was higher than for all other wrist positions. Other wrist positions had no effect on AS; so, for those positions Hypothesis-1 is rejected by the data.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we manipulated the wrist flexion-extension angle thus changing the length of extrinsic muscles, and observed variations in the maximal grip strength according to the classic force-length curve (McMahon 1984). Rather unexpectedly, however, the submaximal, ‘natural’ grip force was independent of the wrist position (Ambike et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, an interpretation has been offered of the force drift (and also of the hand position drift in multi-joint tasks, Zhou et al 2014;Zhou et al 2015) based on the idea of RC control (Ambike et al 2013;Zhou et al 2014;Ambike et al 2015). According to this idea, RC for a performance variable drifts slowly towards the actual value of this variable (RC-back-coupling) reflecting the natural tendency of physical systems to move towards a minimum of potential energy.…”
Section: Unintentional Drift In Variables Without Visual Feedbackmentioning
confidence: 96%
“…Removing visual feedback during steady-state accurate force production tasks is known to lead to a slow drift in the force level (Slifkin et al 2000;Vaillancourt et al 2001;Vaillancourt and Russell 2002;Ambike et al 2013). In those earlier studies, the subjects were not explicitly instructed to correct target forces, while our subjects were always instructed to keep the F TOT and M TOT values at the target level.…”
Section: Unintentional Drift In Variables Without Visual Feedbackmentioning
confidence: 97%
“…The principle has been shown to hold in a variety of experimental conditions (Ambike, Paclet, Latash, & Zatsiorsky, 2013; Niu, Latash, & Zatsiorsky, 2012; Robertson & Johnston, 2012; Shim, Latash, & Zatsiorsky, 2005b). In a recently published paper (Singh, Zatsiorsky, & Latash, 2013) we showed that adaptations to fatigue of a single digit violate the principle of superposition.…”
Section: Introductionmentioning
confidence: 99%